Buckyball-based spherical display of crown ethers for de novo custom design of ion transport selectivity - Li, Ning (2023)
Searching for membrane-active synthetic analogues that are structurally simple yet functionally comparable to natural channel proteins has been of central research interest in the past four decades, yet custom design of the ion transport selectivity still remains a grand challenge. Here we report on a suite of buckyball-based molecular balls (MBs), enabling transmembrane ion transport selectivity to be custom designable. The modularly tunable MBm-Cn (m = 4-7; n = 6-12) structures consist of a C60-fullerene core, flexible alkyl linkers Cn (i.e., C6 for n-C6H12 group), and peripherally aligned benzo-3m-crown-m ethers (i.e., m = 4 for benzo-12-crown-4) as ion-transporting units. Screening a matrix of 16 such MBs, combinatorially derived from four different crown units and four different Cn linkers, intriguingly revealed that their transport selectivity well resembles the intrinsic ion binding affinity of the respective benzo-crown units present, making custom design of the transport selectivity possible. Specifically, MB4s, containing benzo-12-crown-4 units, all are Li+-selective in transmembrane ion transport, with the most active MB4-C10 exhibiting an EC50(Li+) value of 0.13 μM (corresponding to 0.13 mol % of the lipid present) while excluding all other monovalent alkali-metal ions. Likewise, the most Na+ selective MB5-C8 and K+ selective MB6-C8 demonstrate high Na+/K+ and K+/Na+ selectivity values of 13.7 and 7.8, respectively. For selectivity to Rb+ and Cs+ ions, the most active MB7-C8 displays exceptionally high transport efficiencies, with an EC50(Rb+) value of 105 nM (0.11 mol %) and an EC50(Cs+) value of 77 nM (0.079 mol %).